Rab Proteins and the Secretory Pathway: The Case of Rab18 in Neuroendocrine Cells - VAZQUEZ-MARTINEZ, RAFAEL; MALAGÓN, MARIA M. (Frontiers in Endocrinology, 2011)
The secretory pathway is a process characteristic of cells specialized in secretion such as endocrine cells and neurons. It consists of different stages that are dependent on specific transport of proteins in vesicular-tubular carriers. Biochemical analyses have unveiled a number of protein families that confer identity to carrier vesicles and specificity to their transport. Among them is the family of Rab proteins, Ras-like small GTPases that anchor to the surface of transport vesicles and participate in vesicle formation from the donor compartment, transport along cytoskeletal tracks, and docking and fusion with the acceptor compartment. All of these functions are accomplished through the recruitment of effector proteins, such as sorting adaptors, tethering factors, kinases, phosphatases and motors. The numerous Rab proteins have distinct subcellular distributions throughout the endomembrane system, which ensures efficient cargo transfer. Rab proteins act as molecular switches that alternate between a cytosolic GDP-bound, inactive form and a membrane-associated GTP-bound, active conformation. Cycling between inactive and active states is a highly regulated process that enables Rabs to confer spatio-temporal precision to the different stages through which a vesicle passes during its lifespan. This review focuses on our current knowledge on Rab functioning, from their structural features to the multiple regulatory proteins and effectors that control Rab activity and translate Rab function. Furthermore, we also summarize the information available on a particular Rab protein, Rab18, which has been linked to the control of secretory granule traffic in neuroendocrine cells.